Thoracoscopic Resection of Fluorodeoxyglucose-Avid Mediastinal Lymph Nodes Associated with Advanced Ovarian Carcinoma - Hamaji, Masatsugu; Yamaguchi, Ken; Koyasu, Sho; Date, Hiroshi (The Thoracic and Cardiovascular Surgeon, 2019)
The indication for surgery is controversial in patients with advanced ovarian cancer and fluorodeoxyglucose (FDG)-avid mediastinal lymph nodes. Herein we report our experience in thoracoscopic resection of FDG-avid mediastinal lymph nodes associated with advanced ovarian cancer in six patients. No perioperative or long-term mortality was noted. FDG-avid mediastinal lymph nodes in advanced ovarian carcinoma may merit thoracoscopic resection with histological confirmation for more precise staging.
Keywords: ovarian carcinoma; mediastinal lymph nodes; thoracoscopy/VATS